Modelling the toxicity of nanoparticles - Tran, Lang; Bañares, Miguel A.; Rallo, Robert (Springer, 2017)
In today's nanotechnology and pharmaceutical research, alternative toxicology testing methods are crucial for ethically and commercially sound practice. This book provides practical guidelines on how to develop and validate quantitative nanostructure-toxicity relationship (QNTR) models, which are ideal for rapidly exploring the effects of a large number of variables in complex scenarios. Through contributions by academic, industrial, and governmental experts, Modelling the Toxicity of Nanoparticles delivers clear instruction on these methods and their integration and use in risk assessment. Specific topics include the physico-chemical characteristics of engineered nanoparticles, nanoparticle interactions, in vivo nanoparticle processing, and more. A much-needed practical guide, Modelling the Toxicity of Nanoparticles is a key text for researchers as well as government and industry regulators.- Resumé vydavatel
Includes index.
Keywords: nanomateriály; bezpečnostní management; nanočástice; toxicita; nanomaterials; safety management; nanoparticles; toxicity; elektronické knihy; sborníky; electronic books; papers of several authors